Pengaruh Literasi Keuangan, Persepsi Kemudahan Transaksi dan Self-Control terhadap Pengelolaan Keuangan Pribadi Gen Z Pengguna E-wallet : Studi Kasus Gen Z Kabupaten Boyolali - Novi Anna Permatasari (AKUNTANSI 45, 2026)
Financial technology innovation has significantly contributed to the transformation of public payment systems, shifting from conventional transactions to digital transactions. One of the rapidly growing innovations is technology-based platforms that enable users to store funds electronically and conduct cashless transactions. This study examines the role of financial literacy, perceived ease of transaction, and self-control in influencing personal financial management among generation Z e-wallet users in Boyolali Regency. A quantitative approach was employed using primary data collected through an online questionnaire survey. From a total population of 244,640 individuals, 202 respondents were selected using a random sampling technique. The data analysis process included descriptive statistics, instrument testing, classical assumption tests, multiple regression analysis, and hypothesis testing using t-tests and F-tests with the assistance of SPSS version 25. The findings indicate that financial literacy and self-control have a significant relationship with personal financial management. Meanwhile, perceived ease of transaction does not show a significant effect on personal financial management. However, when analyzed simultaneously, all variables collectively demonstrate an influence on personal financial management.